2016
DOI: 10.1002/adfm.201601357
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Origin of Voltage Hysteresis in Conversion Reaction for Na Rechargeable Batteries: The Case of Cobalt Oxides

Abstract: Conversion reaction electrodes offer a high specific capacity in rechargeable batteries by utilizing wider valence states of transition metals than conventional intercalation‐based electrodes and have thus been intensively studied in recent years as potential electrode materials for high‐energy‐density rechargeable batteries. However, several issues related to conversion reactions remain poorly understood, including the polarization or hysteresis during charge/discharge processes. Herein, Co3O4 in Na cells is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 62 publications
1
45
0
Order By: Relevance
“…Sun's group combined graphene with mesoporous Co 3 O 4 particles and the hybrid anode ensured a good capacity (523.5 mAh g −1 ) and good cycle stability at 25 mA g ( Fig. 8 c) [190] . Their Co 3 O 4 -graphene nanoplatelet hybrid anode delivered a high capacity of 756 mAh g −1 with good reversibility ( Fig.…”
Section: Graphene/transition Metal Oxidesmentioning
confidence: 99%
“…Sun's group combined graphene with mesoporous Co 3 O 4 particles and the hybrid anode ensured a good capacity (523.5 mAh g −1 ) and good cycle stability at 25 mA g ( Fig. 8 c) [190] . Their Co 3 O 4 -graphene nanoplatelet hybrid anode delivered a high capacity of 756 mAh g −1 with good reversibility ( Fig.…”
Section: Graphene/transition Metal Oxidesmentioning
confidence: 99%
“…The mismatch in ionic mobility between the two species and the lack of a thermodynamic driving force to redistribute metal ions possibly lead to asymmetrical reaction pathways (different equilibrium potentials), which are the source of large voltage hysteresis . As shown in Figure c, Kim et al found that, after initial cycling, Co 3 O 4 nanocrystals were directly converted into a Co and Na 2 O composite on discharging, while the composite changed back into Co 3 O 4 nanocrystals via an intermediate phase (CoO 1− x ).…”
Section: Challenges For Conversion‐type Anode Materials In Sibsmentioning
confidence: 99%
“…c) Schematic illustration of conversion reaction pathways for Co 3 O 4 in Na rechargeable batteries. Reproduced with permission . Copyright 2016, Wiley‐VCH.…”
Section: Challenges For Conversion‐type Anode Materials In Sibsmentioning
confidence: 99%
“…The thermodynamic sodiation route, from P nanoclusters to NaP chains to layered Na 3 P, involves the breaking and forming of many bonds and should be significantly slower than deintercalation. A similar scheme with kinetic and thermodynamic routes for charge and discharge, respectively, has been described for the Na/Co 3 O 4 system …”
Section: Figurementioning
confidence: 99%